(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The increasingly fierce competition in the cafe business, especially in the pet-friendly cafe segment, requires managers to understand the factors that can increase customer satisfaction and loyalty. Adequate facilities and a comfortable cafe atmosphere are important aspects in creating a positive experience for customers. This study aims to analyze the effect of cafe facilities and atmosphere on customer loyalty through customer satisfaction as a mediating variable at Pawvilion Cafe. The study used a quantitative approach with a survey method by distributing questionnaires to Pawvilion Cafe visitors. The research sample was determined using a purposive sampling technique with the criteria of respondents who had visited the cafe. Data were analyzed using the Partial Least Square Structural Equation Modeling (PLS-SEM) method with the help of the SmartPLS application. The results showed that cafe facilities and atmosphere had a positive and significant effect on customer satisfaction. In addition, facilities, cafe atmosphere, and customer satisfaction also had a positive effect on customer loyalty. Customer satisfaction was proven to mediate the effect of cafe facilities and atmosphere on loyalty. These findings suggest that improving the quality of facilities and creating a comfortable atmosphere can increase customer satisfaction and strengthen customer loyalty. The research findings are expected to provide input for café managers in designing more effective and customer-oriented service strategies.